Improving Broiler Chicken Farming Management in Closed Houses - M. Q. Sa’ad; Sumiati; R. Afnan; R. Fadilah (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Genetic improvements in broiler chickens represent a major advancement in the poultry industry. Through selective breeding techniques, broiler chickens now exhibit remarkably fast growth and improved feed conversion efficiency. Observations were conducted by comparing data from the previous period with suboptimal management and the new period with optimal management. The Coops with good management were observed over one period (approximately 6 weeks). The result were made by comparing the data between the suboptimal management with the improved management, and both sets of data were compared with the international Cobb 2021 standards. The measured variables included: depletion (%), feed consumption (g/bird), body weight (g/bird), feed conversion, performance index, and profit. Improvements in environmental conditions or milieu (temperature, humidity, feed management, water, ventilation, and litter) resulted to more optimal production performance. Depletion, feed consumption, body weight, and feed conversion met the company’s standards (body weight 2.5 kg, feed conversion 1.45, and performance index 450). The final performance was categorized as excellent, with a performance index of 512. Additionally, the profit from the new management was higher at Rp. 9,772 per bird than the old management Rp. 2,570 per bird.